Simplify the expression 2x + 4y − 5z − 5x − 9y + 2z + 4x − 7y + 8z
Expression = 2x + 4x − 5x + 4y – 9y − 7y + 2z + 8z − 5z
= 6x − 5x + 4y − 16y + 10z − 5z
= x − 12y + 5z
total answers (1)
start bookmarking useful questions and collections and save it into your own study-lists, login now to start creating your own collections.
Expression = 2x + 4x − 5x + 4y – 9y − 7y + 2z + 8z − 5z
= 6x − 5x + 4y − 16y + 10z − 5z
= x − 12y + 5z
need an explanation for this answer? contact us directly to get an explanation for this answer